Validation of malay version of sport courage scale and athletic coping skills inventory among silat athletes in Malaysia - Hidrus , Aizuddin (2017)
Coaches and athletes are often focusing on the physical parts in sports and often overlooked the importance of psychological role in advancing our national sports level. Therefore, in order to promote the awareness regarding sport psychology, there are several tools that could be utilised. Questionnaire is one of the important tools used in sport psychology field.In this present study, the Sport Courage Scale (SCS; Konter & Ng, 2012) and the Athletic Coping Skills Inventory (ACSI; Smith, Schutz, Smoll, & Ptacek, 1995) were translated into Malay version and were validated. SCS was developed to measure the level of sport courage among athletes, while ACSI is a well-known inventory to measure the athletes’ coping level. The purpose of this present study was to assess the construct validity and reliability of Malay-version of both SCS and ACSI models among Malaysian Silat athletes by using the confirmatory factor analysis (CFA) and to assess the correlation between them. This study employed the cross-sectional study design. Data collection was done during the 8th UPSI International Pencak Silat Championship 2017 which was held in Tanjung Malim, Perak. The collected data were analysed using CFA with MLR estimator in Mplus statistical software version 7.4. Both models went through some modifications based on CFA results, theoretical support and expert opinions, to fulfil and achieve the model fit status. For SCS-M model, at the end of the analysis, it consisted of three modified latent variables and 26 observed variables with three covariances on items’ residual, yielded RMSEA, SRMR, CFI, and TLI values of 0.033, 0.054, 0.932, and 0.925 respectively. While for ACSI-M, analysis was ended with four latent variables and 18 observed variables with a single covariance on items’ residual. Although the CFI and TLI values were lower than recommended values, 0.898 and 0.878 respectively, yet the RMSEA = 0.053 and SRMR = 0.054, for the last model of ACSIM were satisfactory. As for the correlation between factors of SCS-M and ACSI-M, the highest significant correlated factors were between Self-assured (SCS-M) with Focus on aim (ACSI-M), as well as Self-assured (SCS-M) with Coping with pressure (ACSI-M) by which the r value was 0.405 (p-value < 0.001). Although Coachability (ACSI-M) did not show any significant correlation with any factors from SCS-M, overall result of correlation analysis showed that both SCS-M and ACSI-M were correlated to each other. At the end of the present study, it was concluded that the Malay-version of the SCS-M and ACSI-M models were ascertained to be a valid as well as reliable among Malaysian athletes and also noticed there were correlated to each of the subscales.